Efektivitas Core Stability Exercise dan Balance Strategy Exercise Terhadap Keseimbangan Dinamik Lansia di Komunitas Lansia Bina Asih kelurahan Jagir RW 7 Kecamatan Wonokromo - Martyana Deborah Sanggel; Fransisca Xaveria Hargiani; Puspo Wardoyo; Yohanes Deo Fau (Jurnal Keperawatan Muhammadiyah, 2023)
Objective: The purpose of this research activity is to find out how effective the Core Stability Exercise and Balance Strategy Exercise are on the dynamic balance of the elderly in the Bina Asih elderly community, Jagir sub-district, RW 7, Wonokromo sub-district. Measuring the level of balance dynamically before giving the Core Stability Exercise and Balance Strategy Exercise. Measuring the level of balance dynamically after giving the Core Stability Exercise and Balance Strategy Exercise. Analyzing the effectiveness of Core Stability Exercise and Balance Strategy Exercise on the dynamic balance of the elderlyMethods: The research design that the researchers used in carrying out the process of this research activity was a design called the pre-post test control group design with support for the use of methods using a quasi-experimental approach. Data processing used a pre test as a measuring tool before receiving treatment and a post test after receiving treatment. Pre and post tests were carried out to observe the appearance or presence of inequalities in the increase in dynamic balance experienced in general by the elderly group that occurred before and after the treatment was given using the measurement process using The 3-m Backwards Walk.Results: In testing the elderly group with core stability exercise training, an improvement in The 3-m Backwards Walk (3 MBW) score was obtained as shown in table 1. The mean value before training was 13.6 seconds (SD=3.14), while the mean value after training was 6.8 seconds (SD=2. 18). By using the paired sample t-test, the value of t = 17.312 and p = 0.000 (p<0.05) is obtained, which means there is a significant difference between dynamic balance before and after core stability exercise training. This shows that core stability exercise training provides a significant increase in dynamic balance in the elderly with balance strategy exercise training, an improvement in the 3MBW score was obtained as shown in table 4. The mean before training was 12.45 seconds (SD=1.431), while the mean value after training was 7.96 seconds (SD=1.240). By using the paired sample t-test, the value of t = 37.075 and p = 0.000 (p<0.05) is obtained, which means that there is a significant difference between dynamic balance before and after balance strategy exercise training. This shows that balance strategy exercise training provides a significant increase in dynamic balance in the elderlyThis research is a quasi-experimental research through the use of using data processing, namely using pre- test as data before receiving treatment and post-test after receiving treatment (one group pre-test post-test). Through the presence of pre-test and post-test, the reviewers can obtain objective results in the form of an increase or decrease in results. This research does not require a controlConclusion: Based on the research that has been done, it can be concluded that Core Stability Exercise training and Balance Strategy Exercise training both can improve dynamic balance, but Balance Strategy Exercise training is better at improving dynamic balance than Core Stability Exercise training for the elderly in the Bina Asih Elderly CommunityÂ